Development of a one-run real-time PCR detection system for pathogens associated with poultry infectious diseases - SHIBANUMA, Takuya; NUNOMURA, Yuka; OBA, Mami; KAWAHARA, Fumiya; MIZUTANI, Tetsuya; TAKEMAE, Hitoshi (Journal of Veterinary Medical Science, 2023)
Infectious diseases are an important issue in the poultry industry, requiring early diagnosis and countermeasures. To address this, we present a system based on TaqMan real-time PCR to detect pathogen genome in specimens collected from chickens. We designed 12 primer–probe sets for pathogens causing respiratory or systemic symptoms. In field samples, we detected three viruses, including DNA and RNA viruses, and three bacteria. The chicken anemia virus and Avibacterium paragallinarum were detected only in young and laying hens, respectively. Bacteria were detected only in throat swabs, and gallid alphaherpesvirus 2 was detected in different specimens at each developmental stage. Our novel TaqMan real-time PCR system effectively detects pathogen’s gene in chickens, while taking age into account.